Harvestmen in the semiarid: a new genus and three new species of Pachylinae (Opiliones: Gonyleptidae) from Caatinga dry vegetation, with a cladistic analysis - Nícolas Eugenio de Vasconcelos Saraiva; Marcos Ryotaro Hara; Marcio Bernardino DaSilva (Arthropod Systematics & Phylogeny, 2021)
Abstract Opiliones are highly diverse in the Neotropics. Because of biological constraints, most harvestmen communities are associated with humid forests, exhibiting a high species diversity and endemism in these habitats. Drier formations, such as the Caatinga biome in northeastern Brazil, are less diverse and still considered under-sampled for the order. This study represents an effort to examine the aforementioned diversity by describing a new Gonyleptidae genus, Sertaneja gen. nov., comprising two new species from Ceará state, Sertaneja bicuspidata sp. nov. and Sertaneja crassitibialis sp. nov., and one new species from Rio Grande do Norte state, Sertaneja falcata sp. nov. A morphological cladistic analysis consisting of 20 terminals and 72 characters was performed to evaluate monophyly of the new genus and relate it to other Gonyleptidae. The analysis resulted in a single most parsimonious tree, corroborating Sertaneja gen. nov. monophyly and relatedness to Gyndoides springmanni Soares & Soares, 1947, which in turn is the sister group to the DRMN clade. Taking into account the morphological traits and phylogenetic placement of Sertaneja gen. nov., we chose to place the new genus in Pachylinae despite its polyphyletic status, given that the Sertaneja gen. nov. clade is closely related to one of the Brazilian Pachylinae lineage. A resolution to the Pachylinae conundrum is needed to further explain the subfamily intricacies. Future research requires a larger scope, but currently, based on the new genus monophyly, support, and relatedness, we formally propose its creation and hope to shed light on the possible evolutionary scenarios for the subfamily.